Stabilisation of oleofoams by lauric acid and its glycerol esters. (30th August 2022) - Qiu, Chaoying; Wang, Shaolin; Wang, Ying; Lee, Wan Jun; Fu, Junning; Binks, Bernard P.; Wang, Yong
Highlights: Lauric acid and its glycerides were used as gelators in fabrication of oleofoams. LA and DAG displayed higher over-run than that of MAG and TAG oleogels. DAG-based foam showed smaller bubble size with different melting behavior from TAG. High SFC and unique crystal morphology account for the high overrun of DAG oleofoam. Abstract: Four types of pure lipid, namely lauric acid (LA), glycerol monolaurate (MAG), diglycerol laurate (DAG) and triglyceride laurate (TAG) were used to prepare oleofoams. The relationship between crystal profiles and their performance in oleofoams was established. DAG formed small needle-like crystals while MAG formed large flake-like crystals in oleogels, and crystal shells around air bubbles were observed in LA-, MAG- and DAG-based oleofoams. LA and DAG displayed higher over-run whereas DAG-stabilised foam possessed smaller bubbles and higher physical stability due to the presence of small β and β' crystals. Upon heating, DAG and TAG-based foams showed varying extents of oil drainage indicating the crystals were distributed in a different manner. Therefore, DAG was shown to be an excellent gelator in the fabrication of ultra-stable oleofoams. This work extends the lipid varieties with nutritional features and allows a better understanding on the stabilization mechanisms of lauric acid lipids in oleofoams.